Hematopoietic progenitor cell liabilities and alarmins S100A8/A9‐related inflammaging associate with frailty and predict poor cardiovascular outcomes in older adults - Bonora, Benedetta Maria; Palano, Maria Teresa; Testa, Gianluca; Fadini, Gian Paolo; Sangalli, Elena; Madotto, Fabiana; Persico, Giuseppe; Casciaro, Francesca; Vono, Rosa; Colpani, Ornella; Scavello, Francesco; Cappellari, Roberta; et al. (Aging cell, 2022)
Frailty affects the physical, cognitive, and social domains exposing older adults to an increased risk of cardiovascular disease and death. The mechanisms linking frailty and cardiovascular outcomes are mostly unknown. Here, we studied the association of abundance (flow cytometry) and gene expression profile (RNAseq) of stem/progenitor cells (HSPCs) and molecular markers of inflammaging (ELISA) with the cardiorespiratory phenotype and prospective adverse events of individuals classified according to levels of frailty. Two cohorts of older adults were enrolled in the study. In a cohort of pre‐frail 35 individuals (average age: 75 years), a physical frailty score above the median identified subjects with initial alterations in cardiorespiratory function. RNA sequencing revealed S100A8/A9 upregulation in HSPCs from the bone marrow (>10‐fold) and peripheral blood (>200‐fold) of individuals with greater physical frailty. Moreover higher frailty was associated with increased alarmins S100A8/A9 and inflammatory cytokines in peripheral blood. We then studied a cohort of 104 more frail individuals (average age: 81 years) with multidomain health deficits. Reduced levels of circulating HSPCs and increased S100A8/A9 concentrations were independently associated with the frailty index. Remarkably, low HSPCs and high S100A8/A9 simultaneously predicted major adverse cardiovascular events at 1‐year follow‐up after adjustment for age and frailty index. In conclusion, inflammaging characterized by alarmin and pro‐inflammatory cytokines in pre‐frail individuals is mirrored by the pauperization of HSPCs in frail older people with comorbidities. S100A8/A9 is upregulated within HSPCs, identifying a phenotype that associates with poor cardiovascular outcomes. Frailty affects physical, cognitive, and social domains exposing older adults to adverse health outcomes. High physical frailty with increased S100A8/A9 alarmins level in HSPCs (Hematopoietic Stem/Progenitor cells) and blood identify subjects with early cardiorespiratory dysfunctions. Low HSPCs count and high S100A8/A9 levels in the bloodstream associate with more advanced, multidomain frailty predicting major adverse cardiovascular events (MACE).